2017
DOI: 10.1111/1540-6229.12190
|View full text |Cite
|
Sign up to set email alerts
|

Real Estate Returns by Strategy: Have Value‐Added and Opportunistic Funds Pulled Their Weight?

Abstract: Real estate strategies broadly fall into three categories: core, value‐added and opportunistic. This empirical examination of net returns from these three strategies indicates that, on a risk‐adjusted basis, the value‐added funds have strongly underperformed and the returns from opportunistic funds have weakly underperformed the returns available from core funds. In so concluding, this article departs from standard asset‐pricing models in two important respects: the total risk is used and the cost of borrowing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…Further, if the market is efficient, after adjusting for risk, the difference in returns should disappear. However, these notions have never been formally tested for individual properties, though some evidence at the fund level (Pagliari ) casts doubt on these notions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, if the market is efficient, after adjusting for risk, the difference in returns should disappear. However, these notions have never been formally tested for individual properties, though some evidence at the fund level (Pagliari ) casts doubt on these notions.…”
Section: Discussionmentioning
confidence: 99%
“…These two questions have important implications for investors. Accurate measurements of risk and returns for different types of properties are crucial for the construction of mean–variance efficient real estate portfolios, particularly when many of the largest institutional investors are substantially increasing their allocations to privately traded alternative investments including income producing properties (see, e.g ., Novy‐Marx and Rauh , Pagliari ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found no significant difference in returns and systematic risk across funds with different investment strategies but increased specific risk in more opportunistic funds. On a riskadjusted basis, Bollinger and Palgliari (2019) and Pagliari (2020) found that value-added and opportunistic funds underperform core funds in the United States. Focussing on the role of specialisation, based on European private real estate funds from INREV, Fuerst et al (2021) showed both country specialisation and country-sector specialisation are associated with superior returns while sector specialisation is not.…”
Section: Related Literaturementioning
confidence: 99%
“…NREFs are classified by investment style as opportunistic, value-added and core investment strategy. In a recent study, Pagliari (2020) showed that core funds provide marginally superior risk-adjusted returns to opportunistic funds, whereas value-added funds provided clear underperformance to opportunistic funds.…”
Section: Literature Reviewmentioning
confidence: 99%